THU0211 Adult onset still's disease: a rare association with autoimmune thyroiditis. (1st June 2001) - Cossu, A; Congiu, LA; Capelli, P; Solinas, F; Carcassi, A
Abstract : Background: Adult onset Still's disease (AOSD) was first described by Bywaters in 1971. Subsequently more than 300 cases have been reported. AOSD is a systemic inflammatory disease with high spiking fever, a typical rash and arthritis or arthralgia as major clinical features. The disease is accompanied by a neutrophylic leukocytosis. Other common features are sore throat, intensive myalgias, lymphoadenopathy, hepatosplenomegaly, pericarditis and pleuritis. A 48 years old white woman recently presented to our observation. She had been in her usual state of good health until 7 years before, when she developed fever, arthralgias, sore throat and euthyroid non-toxic goitre. Thyroid antibodies (Thyreoglobulin, microsomal, peroxidase) were elevated. She was diagnosed to have autoimmune thyroiditis and was treated with l-thyroxine and prednisone 25 mg daily. She has done well until eight months ago when she developed fever, arthralgias, sore throat and myalgias. One month later she was admitted to her local hospital with spyking fever of 39, 0°C, pleuritic chest pain, dyspnea, hepatomegaly, palpitations, fatigue and weight loss. Chest radiograph revealed bilateral pleural effusion and echocardiogram demonstrated pericardial effusion. A thoracentesis removed 30 ml of pleuric fluid, wich had the characteristic of an exudate. Ultrasound abdominal investigation revealed mild hepstomegaly. Once with the fever spike (40°C) a mildly pruritic maculopapular evanescent rash located on the extremities was observed and interpreted as drug induced. Laboratory examination revealed haemoglobin 10, 2 g/dl, Erythrocyte mean corpuscolar volume 71, 2 fl, platelet count 628'000/mmc, White blood cell count 30'640/mmc with 96% neutrophils, ESR 76 mm/h, CRP 32, 7 mg/dl, Rheumatoid Factor 121, 0 UI/ml. ANA, ENA, ANCA, ACA and anti-DNA were normal. There was no serological evidence for active o recent infection and blood coltures were negative. Malignancies were excluded. There was no response to empiric antibiotics. Therapy with NSAIDs failed. Treatment with 3, 5‑4, 0 mg/Kg daily Cyclosporine for three months was ineffective. Prednisone 50 mg daily resulted in resolution of fever, systemic manifestations, sore throat and normalisation of her laboratory tests, including Rheumatoid Factor. Rheumatic diseases are, more frequently than suspected, associated with autoimmune thyroiditis. To our knowledge this is the second reported case of association between AOSD and autoimmune thyroiditis. Test for Rheumatoid Factor, ANA and other autoantibodies are generally negative in AOSD. Some criteria for the diagnosis of AOSD consider a positive Rheumatoid Factor as an exclusion criteria. But it may be positive in a transient manner in up to 4 to 6% of those patients. Objectives: Methods: Results: Conclusion: